Evaluation of sealing characteristics of copper gasket using laser microscope with wide field of view - Isami NITTA; Yoshio MATSUZAKI; Yosuke TSUKIYAMA; Motoshi HORITA; Shuichi SAKAMOTO (Nihon Kikai Gakkai ronbunshu, 2014)
To quantitatively predict leakage rates through gasket/flange interface, it is important to observe contact conditions at seal surfaces because the leakage path consists of the non-contact portions between the flange and gasket surfaces. The contact surfaces of the flanges were finished by lathe turning. In this study, we observed real contact area on gasket surfaces using a laser microscope with a wide field of view. The observations indicated that the leakage paths on the gasket surfaces were in the radial direction perpendicular to a lathe-turned groove and the circumferential direction along the groove. As the closing loads increased, the leakage paths in the radial direction disappeared and only the leakage path in the circumferential direction remained. The critical contact pressure where the leakage paths in the radial direction disappear was determined from the observation of the contact surface of the gasket. Over the critical contact pressure, the leakage rates obtained from the experiments showed good agreement with the calculated values under the assumption of laminar flow along the turned groove. Under the critical contact pressure, the recalculated values considered the leakage paths in both the radial and circumferential directions approached the experimental values.